Pengembangan Sikap Prososial melalui Kegiatan Pramuka dalam perspektif Pendidikan Agama Islam - Mustain Syahrul; Wirdati Wirdati (Lembaga Yasin AlSys, 2025)
This study is motivated by the limited research on the development of prosocial behavior through extracurricular activities, despite its vital role in shaping the character and personality of elementary school students. The aim of this research is to describe the implementation of the scouting program, assess the prosocial abilities of fifth-grade students, and explore the contribution of scouting activities in supporting prosocial development from the perspective of Islamic Religious Education (PAI) at SDN 42 Korong Gadang. A qualitative case study approach was used, involving seven participants selected through purposive sampling. Data were collected through in-depth interviews, participatory observation, and documentation, and analyzed using an interactive analysis technique, including data reduction, data display, and conclusion drawing. The findings show that the scouting program is implemented in a structured manner through routine and special activities such as Perjusami (weekend camp), and effectively fosters students' prosocial attitudes reflected in enhanced empathy, responsibility, cooperation, and social awareness. These findings reinforce the relevance of social learning theory and emphasize the importance of integrating religious values in character education. The study concludes that scouting activities serve as an effective medium for developing prosocial behavior through a combination of scouting training and the internalization of Islamic values. The implications include strengthening the theoretical foundation of religious-based character education and offering practical recommendations for schools and scout leaders to design more meaningful and transformative scouting programs.